Abnormal displacement of discoid lateral meniscus with snapping knee detected by full extension and deep flexion MRI: Report of two cases - Yusuke Hashimoto; Nishino Kazuya; Junsei Takigami; Shinya Yamasaki; Tomohiro Tomihara; Nagakazu Shimada; Hiroaki Nakamura (Elsevier, 2020)
We evaluated the abnormal displacement of a complete discoid lateral meniscus in two patients with symptoms of a large popping sound during knee flexion and extension, so-called "snapping", and no displacement of the discoid meniscus on routine Magnetic Resonance Imaging (MRI) analysis. MRI images indicated an anterocentral shift of the lateral discoid meniscus on knee deep flexion in one case and a posterocentral shift of the meniscus on knee full extension in the other case. Abnormal meniscal instability was confirmed under arthroscopy in both knees. After arthroscopic partial meniscectomy, one case of posterior horn instability was treated with an inside-out arthroscopic technique, whereas the other case of anterior horn instability was treated with an all-inside repair technique. We conclude that the symptom of a large popping sound during knee motion may indicate abnormal displacement of a complete discoid lateral meniscus and that further MRI analyses on knee full extension and deep flexion may reveal discernible meniscal displacement.